Two Feminist Waves and Two Cultures in Little Women: An Adaptation Studies - Angelina Susanto (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study explores the adaptation of Louisa May Alcott's Little Women into a 2022 Korean television series, focusing on feminist themes across cultural contexts. By examining the portrayal of women's choices and roles, the research reveals how feminist ideas are reimagined for contemporary audiences. Both the novel and the series portray second-wave feminism through characters like Jo March, who challenges traditional gender roles, and third-wave feminism through characters like Meg March, who emphasizes autonomy and personal agency. The Korean series, featuring characters like Oh In-joo and Oh In-hye, illustrates the interplay between traditional values and modern feminist discourse. This study highlights the cultural reinterpretation of feminist values in adaptations.